Burn inhalation injury and intubation with dexamethasone-eluting endotracheal tubes modulate local microbiome and alter airway inflammation - Gonzales, Gabriela; Malka, Ronit; Bizios, Rena; Dion, Gregory R.; Guda, Teja (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundInhalation injuries, caused by exposure to extreme heat and chemical irritants, lead to complications with speaking, swallowing, and breathing. This study investigates the effects of thermal injury and endotracheal tube (ETT) placement on the airway microbiome and inflammatory response. A secondary aim is to assess the impact of localized dexamethasone delivery via a drug-eluting ETT to reduce laryngeal scarring.MethodsInhalation injury was developed in swine by administering heated air (150°C–160°C) under endoscopic visualization. Following injury, segments of regular or dexamethasone-loaded endotracheal tubes (ETTs) were placed in the injured airways for 3 or 7 days. Computed tomography (CT) scans were used to assess airway narrowing post-injury. Biofilm formation on the ETTs was investigated using micro-CT and microscopy. The airway microbiome was analyzed via 16S rRNA sequencing. Inflammatory markers were quantified using an immunoassay and macrophage populations in laryngeal tissue were assessed with CD86 and CD206 staining. Tracheal tissues were also histologically examined for epithelial thickness, collagen area, and mucin production.ResultsCT scans confirmed airway narrowing post-injury, particularly around ETT sites. Biofilm formation was more extensive on dexamethasone-coated ETTs at later timepoints. Beta diversity analysis revealed significant shifts in microbial composition related to ETT type (R2 = 0.04, p < 0.05) and duration of placement (R2 = 0.22, p < 0.05). Differential abundance analysis demonstrated significant positive log fold changes in genera such as Bergeriella, Peptostreptococcus, and Bacteriodes with thermal injury over time. Inflammatory markers IFN-γ, IL-4, and IL-1β were elevated in dexamethasone-ETT groups at 3 days, then decreased by 7 days. Macrophage markers CD86 and CD206 were significantly greater in dexamethasone groups compared to regular ETT groups at 7 days (p = 0.002 and p = 0.0213, respectively). Epithelial thickness was significantly greater with regular ETT placement compared to dexamethasone ETT placement in the burn-injured airway at 3 days (p = 0.027).ConclusionThermal inhalation injury and ETT placement significantly impact airway inflammation, structural integrity, and microbiome composition. Dexamethasone-eluting ETTs, intended to reduce inflammation, increased biofilm formation and elevated cytokine levels, suggesting complex interactions between the drug coating and the host immune response. The airway microbiome shifted significantly with specific taxa thriving in the inflamed environment.